Adaptasi Sosio-Ekologis dan Implementasi Etika Lingkungan di Kelurahan Kahuripan Kota Tasikmalaya - Ita Minarti; Rina Nurul Azmi; Shanaz Dwina Afiyah; Vita Rosita Sari; Helia Dwiputri; Yani Sri Astuti (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This study discusses the convergence between sustainable development and ecological preservation in Kahuripan Village, Tasikmalaya City. The socio-ecological adaptation of the Kahuripan community involves social, economic and physical environmental aspects, with a focus on community participation, social change and social welfare. Implementation of environmental ethics is the key to maintaining a balance between development and environmental sustainability. The research method used is descriptive with a qualitative approach. The research results show that the socio-ecological adaptation of the Kahuripan community involves the practice of conserving natural resources, reducing negative impacts on the environment, building green infrastructure, and environmental education. Despite efforts such as processing organic waste, saving water, and environmental cleanliness activities, there are still challenges such as lack of greenery and awareness in waste disposal. The convergence between sustainable development and ecological preservation in Kahuripan Village is important to maintain a balance between economic, social and environmental development and to become an example for other regions in efforts to achieve sustainable and environmentally sound development.